DAMPAK NEGATIF NIKAH SIRRI DAN AKIBAT HUKUMNYA - Marisa, Kiki; Mulyawan, Fitra (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Public knowledge of the values contained in marriage is still very lacking, they still think that personal problems do not require government/state intervention. There is parental concern about their children who have been closely associated with their prospective husband/wife, so that it is feared that negative things will happen that are not desired, then they are married secretly and not registered at the religious affairs office (KUA). There is no permission from the wife and the religious court for people who intend to marry more than one person. There is excessive parental concern about their child's match, because their child is immediately married because with a hope that at some point if they have reached the specified age limit, then the new marriage will be carried out in accordance with the provisions that have been set.Keywords: Negative, Secret Marriage, Legal Consequences.